The Influence Of Work Engagement And Self-Efficacy On Employee Innovative Performance At SMK Prakarya Internasional - Ary Yanuarti (STMIK Indonesia Banda Aceh, 2026)
This study analyzes the influence of work engagement and self-efficacy on innovative work behavior of education employees at SMK Prakarya Internasional. Using quantitative method with survey on 83 employees population. Descriptive statistics show work engagement score of 4.12 (good category), self-efficacy 4.45 (very good), and innovative performance 4.44 (very good). All instruments are valid (r count > 0.2170) and reliable (Cronbach's Alpha > 0.70). Classical assumption tests meet normality, heteroscedasticity, and multicollinearity requirements. The results show work engagement has positive and significant effect with regression coefficient of 0.644 (t=32.863, sig.0.000). Self-efficacy has positive and significant effect with regression coefficient of 0.611 (t=9.063, sig.0.000). Simultaneously both variables contribute 94.8% to employees' innovative work behavior (R²=0.948), while 5.2% influenced by other variables. These findings become recommendations for strengthening HRM practices through team building programs, competency development, reward systems, and optimization of industry partnerships.